OPTIMIZATION OF BLADEROLLERPARAMETERSFOR SLIDINGCUTTING (Irrigation and Melioration, 2026)
This study advances a rigorous theoretical framework for the sliding cutting mechanismexecuted by a blade mounted on a rotating roller, with the objective of intensifying the efficiencyof soil clod comminution in agricultural systems. Particular emphasis is placed on the kinematiccoupling between tangential and angular velocity components of the cutting edge, alongside a detailedexamination of contact-point dynamics and the nonlinear influence of a variable cutting radius. Theinvestigation further elucidates the kinematic transformation of the effective sharpening (rake) angleunder sliding cutting conditions and its consequent impact on stress-strain localization, fracture initiation, and the evolution of cutting resistance. It is theoretically substantiated that the superpositionof a tangential velocity component induces a transition from predominantly compressive loading toshear-dominated failure mechanisms. This transition significantly reduces the effective tool-materialcontact interface, amplifies stress concentration, and promotes microcrack nucleation and propagationin low-moisture, brittle soil aggregates. Through analytical modeling and parametric optimization,the study establishes the optimal geometric and kinematic configurations of the blade-roller system,including blade inclination, roller diameter, and translational velocity regimes. The results demonstrate that the rational coordination of these parameters yields a pronounced decrease in cuttingresistance, enhanced fragmentation uniformity, and a measurable reduction in specific energy consumption. Overall, the findings provide a mechanistically grounded and quantitatively substantiatedbasis for the design and optimization of energy-efficient soil tillage implements, thereby contributingto the advancement of sustainable and high-performance agricultural processing technologies.